On the revocation of U-Prove tokens - Paquin, Christian (Microsoft Research, 2014)
U-Prove tokens provide many security and privacy benefits over conventional credential technologies such as X.509 certificates. Like any long-lived credentials, there might be a need to revoke issued U-Prove tokens before they expire. Achieving this might seem counterintuitive: how can you revoke an identity when users are anonymous or pseudonymous? This paper explores various revocation mechanisms compatible with the U-Prove technology, to help system designers select the best one for their applications. All of these mechanisms can be implemented today with the core and extensions U-Prove C# SDKs.